Al-AâZAMÄª DAN FENOMENA QIRAAT ALQURAN: ANTARA MULTIPLE READING DENGAN VARIANT READING - Yusuf, Khaeruddin (Hunafa: Jurnal Studia Islamika, 2014)
Absract: This article discusses one of the phenomena in the sciences of the Quran employing the point of view of Â the contemporary muslim scholar, Muá¸¥ammad Muá¹£á¹ÄfÄ al-AâzamÄ«. He asserted Â that one of the entrances used by the Orientalist to assault the authenticity of the Quran was through qiraat phenomenon. Al-AâzamÄ« critisized the Orientalistâs views in terms of methodology, of analysis process and ofÂ  study results. The nonexistance of a dot and diacriticals did not become a problem for the text of the Koran since the system of the true recitation was taught by the prophet through memorization. The true system of reciting the Qurâan had already existed Â in the minds of the Companions of the Prophet. The terms used in recitation cannot also be separated from Al-AâzamÄ«âs attention. He said Â that the term Â âmultipleâ (many) recitaions is more properly usedÂ  than the Â term âvariantâ (various) recitations.Kata Kunci: qiraat, multiple qiraat, tanda titik, diakritikal